Pneumonia in myasthenia gravis: Microbial etiology and clinical management - Su, Manqiqige; Jin, Shan; Jiao, Kexin; Yan, Chong; Song, Jie; Xi, Jianying; Zhao, Chongbo; Zhou, Zhirui; Zheng, Jianming; Luo, Sushan (Frontiers in Cellular and Infection Microbiology, 2022)
Patients with myasthenia gravis (MG) are prone to the development of pneumonia due to long-term immunotherapies and the tendency for aspiration. Pneumonia remains a risk factor for MG worsening and even the most prevalent cause of mortality in MG patients. The pathogen classification and the exploration of the risk factors for mechanical ventilation (MV) may aid in improving the clinical outcome. Between January 2013 and October 2022, an inpatient database review for MG patients with pneumonia concurrence was performed in a tertiary research centre for neuromuscular disorders. Clinical and microbiological characteristics of 116 MG patients with pneumonia were retrospectively analyzed. In our cohort, 90.32% (112/124) of organisms were bacteria and 42.86% (48/112) of pathogenic bacteria were carbapenem-resistant. Epstein–Barr virus (EBV) was detected with high abundance in the next-generation sequencing (NGS) in 12 patients, while cytomegalovirus (CMV) was detected in 8 patients. Non-fermentative gram-negative bacilli were the most prevalent microorganisms, in which ampicillin, sulfamethoxazole-trimethoprim (SMZ-TMP), piperacillin, cefoperazone, ceftazidime and cefepime may have an anti-infectious effect. Besides, peripheral lymphocyte percentage (OR 0.88, 95% CI 0.75 0.96, p=0.02) and serum globulin (OR 1.16, 95% CI 1.02 1.35, p=0.03) were significantly associated with the risk of MV demand. Our identification of the microbial aetiology of pneumonia in MG patients may provide future perspectives on accurate antibiotic options and early interventions of the risk factors.